Comparative perceptions of sexual harassment among athletes across different competitive levels - Zach, Sima; Davidovitz, Maayan; Cohen, Rona (Frontiers in Sports and Active Living, 2024)
Purpose. Despite evidence that sports arenas are grooming ground for sexual harassment, consensus is still lacking what this term constitutes. The aim of this study is to examine how athletes of different levels and non-athletes perceive sexual harassment in sports through the lens of the Institutional Theory. Method. Hundred and thirty pre-service physical education teachers (competitive and non-competitive athletes) and 53 Olympic athletes, rated 27 items divided into four levels of sexual harassment regarding men coaches' behaviors towards women athletes, on a scale of 1 (does not constitute sexual harassment) to 4 (constitutes sexual harassment to a great extent). Findings. Non-Olympic athletes rated the behaviors as constituting sexual harassment to a greater degree than Olympic athletes, in all categories, as did women participants compared to man. Both genders rated sexual harassment and exploitation as the most severe factor followed by Sexist behavior, yet the more competitive the athletes, the less they perceived such behaviors as disturbing. The Professional contact factor was rated as the least disturbing, with women rating it as less disturbing than men. Conclusions. The study underscores the ambiguity surrounding the definition of sexual harassment in sports, emphasizing the necessity for clear boundaries to establish acceptable behavior. Such clarity is essential to ensure that all athletes feel safe within the sporting environment. It emphasizes the importance of zero tolerance for all harassing behaviors, regardless of severity, and the implementation of comprehensive policies and training programs in sport organizations. Moving forward, promoting respect, safety, and awareness, along with ongoing research and evaluation, are crucial for creating inclusive and safe sporting environments.